IMPACT OF TREATMENT OF UNCOMPLICATED MALARIA BY AMODIAQUINE−ARTESUNATE (AS-AQ) ON PFCRT 76T AND PFMDR1 86Y MUTATIONS SELECTION IN PLASMODIUM FALCIPARUM ISOLATES, REPUBLIC OF GUINEA. (12th February 2017) - Diawara, Elisabeth; Beavogui, Abdoul; Camara, Daouda; Sylla, Malick; Yattara, Mohamed; Sow, Amadou; Camara, Gnèpou Camara; Diallo, Saliou; Doumbo, Ogobara; Djimde, Abdoulaye
Abstract : Background: The use of Amodiaquine monotherapy is associated with the selection of resistance markers ( Pfcrt and Pfmd r1). The decrease in sensitivity and the emergence of Plasmodium falciparum -resistant strains have been reported. It is therefore important to know the impact of treatment of uncomplicated malaria with amodiaquine−artesunate (AQ−AS) on Pfcrt 76T and Pfmdr 1 86Y mutations strains of P. falciparum. Methods: We applied the standard protocol of 28 days of WHO 2003, to determine the in vivo efficacy of the combination AQ−AS. In total 170 subjects were included in the study. Molecular analysis focused on 168 dried blood spots. The aims were to determine the frequency of Pfcrt 76T and Pfmdr 1 86Y mutations, to determine the rates of reinfection using polymorphism markers MSP1, MSP2, and microsatellite CA1, Ta87, TA99. Nested PCR followed in some cases by a restriction enzyme. Results: The level of P. falciparum clinical response was 92.85% (156/168) of ACPR before molecular correction and 7% (12/170) LPF. The ACPR after molecular was 97.01% (163/168). The frequency of mutation point Pfcrt 76T was 76.19% (128/168) before treatment and 100% (7/7) after treatment, p=0.14. For Pfmdr 1 mutation the frequency was 27.97% (47/168) before treatment and 60% (6/10) after treatment, p=0.03. Rate of Pfcrt 76T + Pmdr 1 86Y was 22.02% (37/168) before and 50% (6/12) after treatment p=0.003. Conclusions: Despite the combination of AQ with AS, the treatment selected Pfcrt 76T and Pfmdr 1 86Y mutations in Guinea.